The Conception of Managing the innovation Development of an Organization in a Digital Economy from the Perspective of Innovation Culture - Hrynko Pavlo L. (Bìznes Inform, 2020)
The article solves an important scientific-practical task in developing the conception of managing the innovation development of an organization from the perspective of the innovation culture in a digital economy. It is specified that the developed innovation culture in the form of the application of modern ways of organizing the workspace, efficient interaction of staff and the system of motivation should become a solid foundation, allowing organizations effectively introduce innovations and avoid copying the competitors’ strategies, turnover of staff, loss of profitability. The place of innovation culture in a digital economy is considered, as the leading role and importance belongs to the staff of organization, and the success of innovation is, first of all, ensured by the existing efficient innovation culture in the organization that provides an innovation and creative way of thinking to its employees and top management. The contentual details of the category of «innovation culture» at macro- and micro levels as a significant component of the potential of innovation development of organizations are defined more exactly. The principles of building an innovation culture in organizations are proposed, united by three components: «efficient communication», «comfortable working conditions» and «motivation system», which include measures to improve management efficiency. The conception of innovation progressiveness in the form of a survey to determine the innovation and technical development of an organization is recommended for use by entrepreneurs and top management.